Nicotinic alpha 7 receptor agonists EVP-6124 and BMS-933043, attenuate scopolamine-induced deficits in visuo-spatial paired associates learning - Weed, Michael R.; Polino, Joseph; Signor, Laura; Bookbinder, Mark; Keavy, Deborah; Benitex, Yulia; Morgan, Daniel G.; King, Dalton; Macor, John E.; Zaczek, Robert; Olson, Richard; Bristow, Linda J. (PLOS ONE, 2017)
Agonists at the nicotinic acetylcholine alpha 7 receptor (nAChR α7) subtype have the potential to treat cognitive deficits in patients with Alzheimer’s disease (AD) or schizophrenia. Visuo-spatial paired associates learning (vsPAL) is a task that has been shown to reliably predict conversion from mild cognitive impairment to AD in humans and can also be performed by nonhuman primates. Reversal of scopolamine-induced impairment of vsPAL performance may represent a translational approach for the development of nAChR α7 agonists. The present study investigated the effect of treatment with the acetylcholinesterase inhibitor, donepezil, or three nAChR α7 agonists, BMS-933043, EVP-6124 and RG3487, on vsPAL performance in scopolamine-treated cynomolgus monkeys. Scopolamine administration impaired vsPAL performance accuracy in a dose- and difficulty- dependent manner. The impairment of eventual accuracy, a measure of visuo-spatial learning during the task, was significantly ameliorated by treatment with donepezil (0.3 mg/kg, i.m.), EVP-6124 (0.01 mg/kg, i.m.) or BMS-933043 (0.03, 0.1 and 0.3 mg/kg, i.m.). Both nAChR α7 agonists showed inverted-U shaped dose-effect relationships with EVP-6124 effective at a single dose only whereas BMS-933043 was effective across at least a 10 fold dose/exposure range. RG3487 was not efficacious in this paradigm at the dose range examined (0.03–1 mg/kg, i.m.). These results are the first demonstration that the nAChR α7 agonists, EVP-6124 and BMS-933043, can ameliorate scopolamine-induced cognitive deficits in nonhuman primates performing the vsPAL task.